Conversation Analysis in Psychotherapy Research: A Methodological Review - İlknur Dilekler (Psikoloji Çalışmaları)
Conversation analysis is a qualitative research method developed in social sciences that inspects naturally occurring conversations and reveals the particular characteristics of conversationalists’ interactions. Psychotherapy research aims to understand the features that determine the psychotherapy process and its effectiveness by using many different qualitative and quantitative research methods. The characteristics of interactions between psychotherapists and clients in psychotherapy are one of these features, and conversation analysis has become one of the methods used in psychotherapy research. Although conversation analysis in Turkey is better known as a research method in sociology, educational sciences, and various subfields of psychology, there is a lack of Turkish resources on the kind of questions conversation analysis can answer in psychotherapy research. Hence, the current article provides theoretical and methodological information about how conversation analysis is utilized in psychotherapy research and reviews the literature. Studies examining psychotherapy interactions using this method belong to the psychotherapy research tradition based on hermeneutics. Conversation analysis makes inferences about how therapists and clients jointly construct the psychotherapy process and how changes take place using its unique assumptions and analysis methods. In the psychotherapy research literature, conversation analysis studies have sought answers to many questions. The research hitherto has evolved around three main areas of study: therapeutic interventions, elements of the therapeutic relationship, and the effects of psychotherapy. In this paper, the literature findings are summarized and the implications of these studies for the practice of psychotherapy and recent research trends are touched upon. Furthermore, the analysis of a Turkish psychotherapy extract is illustrated. Finally, the article concludes that conversation analysis in psychotherapy makes noteworthy contributions to individually and culturally tailored psychotherapy practice. Research on psychotherapy outcomes and mixed-method designs are expected to become prominent in the future.